Age of Acquiring Causal Human Papillomavirus (HPV) Infections: Leveraging Simulation Models to Explore the Natural History of HPV-induced Cervical Cancer. (20th May 2017) - Burger, Emily A; Kim, Jane J; Sy, Stephen; Castle, Philip E
Summary: Although new HPV infections and associated precancers can occur throughout a woman's lifetime, only a small proportion are acquired in mid-adult women and are vaccine-preventable. Our model-based explorations provide insight into causal HPV infections and highlight the potential limitations of using surrogate endpoints for vaccine efficacy studies of mid-adult women to guide policy decisions for implementation. Abstract: Background: Although new human papillomavirus (HPV) infections can occur at all ages, the age at which women acquire their "causal" HPV infection that develops into cervical cancer is poorly understood and practically unobservable. We aimed to estimate the age distribution at which individuals acquired their causal HPV infection in the absence of HPV vaccination or screening to help guide the optimal use of both. Methods: Using an empirically calibrated mathematical model that simulates the natural history of cervical cancer, we estimated the cumulative number of causal HPV infections by age, stratified by HPV genotype (HPV16 vs. other HPV genotypes), and the direct age-specific reduction in cancer incidence for alternative vaccination initiation scenarios (i.e., age 9–45 years). Results: Our model projected that among all cervical cancers, 50% and 75% of women acquired their causal HPV infection by ages 20.6 (range: 20.1–21.1) and 30.6 (range: 29.6–31.6) years, respectively. HPV16 infections were acquired at an earlier age. Assuming 95% efficacy against HPV16 and HPV18 infections, the direct reduction in lifetime risk of cervical cancer varied from 55% (53–56%) among women vaccinated at age 9 years to 6% (range: 6–7%) among women vaccinated at age 45 years. Similar patterns were observed for the second-generation vaccine. Conclusions: Although new HPV infections and precancers can occur throughout a woman's lifetime, only a small proportion are acquired in mid-adult women and are vaccine-preventable. Our simulations highlight the potential limitations of using surrogate endpoints for vaccine efficacy studies of mid-adult women to guide policy decisions for implementation.